2001
DOI: 10.1023/a:1013175516793
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A major obstacle in the clinical management of malignant melanoma is its intrinsic resistance to chemotherapy and radiation therapy. Consequently, most patients with melanoma often do not respond to conventional anticancer therapy in a clinically significant manner. Recent advances in cancer research have provided new insights into the mechanisms of intrinsic resistance in melanomas. We have recently reported that the over-expression of tyrosinase-related protein 2 (TYRP2), an enzyme that is well characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Recently, there were some reports that TRP-2 overexpression was associated specifically with resistance to DNA-damaging drugs and radiation treatment (Chu et al, 2000;Pak et al, 2000Pak et al, , 2001Pak et al, , 2004. We also reported recently that compared to patients receiving either chemotherapy or vaccinations alone, glioblastoma patients who received chemotherapy after active immunological DC-based vaccination experienced slower tumor progression and longer survival times .…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Recently, there were some reports that TRP-2 overexpression was associated specifically with resistance to DNA-damaging drugs and radiation treatment (Chu et al, 2000;Pak et al, 2000Pak et al, , 2001Pak et al, , 2004. We also reported recently that compared to patients receiving either chemotherapy or vaccinations alone, glioblastoma patients who received chemotherapy after active immunological DC-based vaccination experienced slower tumor progression and longer survival times .…”
Section: Introductionmentioning
confidence: 77%
“…TRP-2 overexpression has been shown to mediate resistance to treatments that evoke DNA damage (Chu et al, 2000;Pak et al, 2001). Melanoma cells that overexpressed TRP-2 generated resistance not only to chemotherapeutic drugs but also to X-ray-and ultraviolet (UV)-radiation-induced apoptosis (Nishioka et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosinase, TRP-1, as well as TRP-2 are melanogenesis enzymes which mediate the conversion of L-tyrosine to melanin. In particular, TRP-2 has been reported to be abundantly expressed in most tumors and melanoma cell lines (Pak, Chu, Lu, Kerbel, & Ben-David, 2001). It has been reported that some phenolic depigmenting compounds are not only tyrosinase inhibitors, but also agents that decreased MITF production with synergistic effects on melanogenesis (Solano, Briganti, Picardo, & Ghanem, 2006 also be beneficial to human skin (Lephart, Sommerfeldt, & Andrus, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…32) Therefore, 2,3-dihydro-4Ј,4ٞ-di-O-methylamentoflavone (5) is believed to affect the cytotoxicity of melanogenic intermediates in melanocytes, 33) which may therefore reduce pigment production. The pigment-related gene expression of this compound was also evaluated.…”
Section: The Effects Of Anti-tyrosinase Activities and Melanin Inhibimentioning
confidence: 99%